Jihadist beheading: a convergence of technology, theology, and teleology? - Lentini, Pete; Bakashmar, Muhammad (Routledge, 2007)
Although contemporary jihadist terrorists are most well known for perpetrating operations that generate mass casualties, they also conduct violent acts that yield fewer victims, such as beheading hostages. Examining the religious and cultural contexts that surround jihadist beheadings, developments in new media, and drawing on examples from the ChechenWars and the IraqWar, this article argues that jihadists have employed this tactic for a range of reasons, including obtaining ransom payments, hampering foreign investment, discrediting transitional states, and recruiting supporters. It also suggests that jihadists’ beheading of their captives corresponds with aspects of cosmic war, particularly on how religious terrorists’ desires to please a deity and secure a place of honor in the hereafter has devalued the lives of both captor and prisoner. Consequently, contemporary jihadist beheading is an outgrowth of the practice of terrorist hostage taking. As this article goes to press (February 2007) UK authorities disrupted a terrorist cell allegedly plotting to behead British Muslim soldiers who served in Afghanistan and Iraq, and to broadcast the filmed executions through jihadist websites. Journalists have described the intended beheadings and their dissemination as “Iraq-style.” There is no doubt that jihadist beheading became more widely known as a result of the Iraq conflict. However, the beheadings in Iraq were largely used to recruit future jihadists and to demonstrate jihadists’ strength to their potential support base, the global Muslim community. In contrast, the alleged UK beheading plot was aimed at striking terror into Muslims living in the UK so that they would not support or serve their government. Indeed the Iraq beheadings were intended to persuade, and the UK plot was intended to dissuade. These alleged activities suggest that contemporary jihadist beheading is not only an extension of hostage-taking, it is also an independently evolving terrorist tactic.